(untitled) - Water, Mark (Hong Kong, 2000)
Although the book of Genesis can seem large and overwhelming, this handy little pocket guide provides a quick overviewÂ it examines the purpose, personalities, geographical places, and teachings of the book of Genesis. Full color photos, illustrations, and charts help the reader see, at a glance, interesting and important biblical information on Genesis. Thirty-one subjects are examined. A 7-panel fold-out chart provides an outline of the book of Genesis and a 7-week reading plan. It is an ideal resource for Bible study groups, new Christians, seekers, Sunday school gifts, and Bible teachers.
Keywords: Bible